2000
DOI: 10.1017/s1368980000000161
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity of botanicals

Abstract: Objective: Hepatic impairment resulting from the use of conventional drugs is widely acknowledged, but there is less awareness of the potential hepatotoxicity of herbal preparations and other botanicals, many of which are believed to be harmless and are commonly used for self-medication without supervision. The aim of this paper is to examine the evidence for hepatotoxicity of botanicals and draw conclusions regarding their pathology, safety and applications. Design: Current literature on the hepatotoxicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(85 citation statements)
references
References 89 publications
(92 reference statements)
3
78
0
4
Order By: Relevance
“…This finding has not been described before for chronic intoxication with Kh fruit. It has been described that several plants as Larrea tridentata (Stickel et al, 2000), and Ruta graveolens (Serrano-Gallardo et al, 2013) can cause a hepatotoxic effect similar to the necrotic damage observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…This finding has not been described before for chronic intoxication with Kh fruit. It has been described that several plants as Larrea tridentata (Stickel et al, 2000), and Ruta graveolens (Serrano-Gallardo et al, 2013) can cause a hepatotoxic effect similar to the necrotic damage observed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…However, there is low interest in the toxic manifestations brought about by natural products due to the unfounded belief that drugs obtained from nature are devoid of any toxic ramifications. 2 Moringa oleifera is a plant that originates in Asia but is nowadays cultivated extensively in various parts of the world. Thus, the plant goes by many names; benzolive tree, morunga, drumstick tree, nebeday among others.…”
Section: Introductionmentioning
confidence: 99%
“…Germander (Teucrium chamaedrys) extracts cause DILI, probably mediated by furano neoclerodane diterpenoids [9] . Chaparral is a desert shrub traditionally used by Native Americans for treatment of several ailments.…”
Section: Discussionmentioning
confidence: 99%